(untitled) (Perner’s Contacts, 2011)
The use of one-dimensional CFD engine simulation is an essential tool to the engine development process. Engine design through simulation can drastically reduce time needed to perform engine experiments and prototyping, as most engine experiments can be simulated within the software.